1991
DOI: 10.1007/bf02337773
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary human myopathies in muscle culture

Abstract: In this article I illustrated the use of regenerating human muscle cultures for studying the hereditary human myopathies. Although some of the data are still controversial, they do point up the great potential of this "in vitro system". For hereditary myopathies due to developmentally regulated proteins that are expressed only at a more advanced stage of muscle differentiation, the use of highly differentiated nerve-muscle cocultures might contribute significantly to a better understanding of their development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…All day-8 myotubes expressed immunoreactivity for fast heavy myosin and only a few myotubes expressed slow heavy myosin. These observations are consistent with the histochemical findings described by Askanas et al (1) and Meola et al (31), indicating that aneural Sc-culture differentiation to slow fibers is blocked by a missing factor. It could be speculated that this missing factor might be innervation or activity, since in vivo studies show that these factors are necessary to obtain a full slow phenotype (32).…”
Section: Discussionsupporting
confidence: 93%
“…All day-8 myotubes expressed immunoreactivity for fast heavy myosin and only a few myotubes expressed slow heavy myosin. These observations are consistent with the histochemical findings described by Askanas et al (1) and Meola et al (31), indicating that aneural Sc-culture differentiation to slow fibers is blocked by a missing factor. It could be speculated that this missing factor might be innervation or activity, since in vivo studies show that these factors are necessary to obtain a full slow phenotype (32).…”
Section: Discussionsupporting
confidence: 93%
“…Isolated Sc's can proliferate, fuse and differentiate into human myotubes and can be kept in culture for weeks. Sc's were initially used in studies of muscle cell development and regeneration as well as in studies of inherited metabolic disorders with identified biochemical defects; however, they have also been used in studies of enzyme defects that affect multiple organ systems [please refer to review ]. Later, human myotube cultures were used in metabolic and signal transduction studies .…”
Section: Human Myotubes As a Model For Skeletal Musclementioning
confidence: 99%
“…Cell cultures were prepared as previously described (Meola G 1991) from muscle biopsies obtained from patients with congenital and adult forms of myotonic dystrophy types 1 and 2 to study the differentiation and replicative capacity of mutant DM1 and DM2 myoblasts in culture under different conditions.…”
Section: Cell Culturesmentioning
confidence: 99%